Análisis del sistema de iluminación del Hospital Julius Doepfner de la ciudad de Zamora. - Morocho Piedra, César Augusto (2013)
In the present investigation, the diagnosis was performed for system the illumination in the Julius Doepfner Hospital in the Zamora city, measuring main parameters of illumination, allowed us to propose economic technical solutions. The design of the new illumination system was developed in Dialux software, it allows real-time simulation and interaction and manipulation of the environment in a smooth and agile. It was determined that the illumination system of the Hospital owns 8% of the total installed load, when according to the International Commission On Illumination (CIE) should occupy 20% of the total load installed in a hospital, average illuminance levels (Em) in Julius Hospital environments Doepfner meet the UNE EN 12464-1, 2003 on 41.61%; likewise the electrical power density for illumination (DPEA), meets at 81% and the energy efficiency of the installation (VEEI) meets at 57%. It is important to note that the selected luminaires, for the design of the illumination system must be brand Philips TL5, by having 25,000 hours of life, besides being efficient and save up 25% to 40% that T8 and T12. To preserve the illumination system in top condition, there must be in the Julius Doepfner Hospital a team of illuminance measuring and ongoing maintenance of the system.